2014
DOI: 10.1136/bjsports-2014-093494.166
|View full text |Cite
|
Sign up to set email alerts
|

The Nordic Football Injury Audit: Higher Injury Rates for Professional Football Clubs With Third-Generation Artificial Turf at Their Home Venue

Abstract: Hagglund, M. (2013

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…16,27,28 Nevertheless, evidence remains indicating persistent differences between injuries sustained on the two different surfaces. [29][30][31][32][33] None of these studies reported what characteristics of the playing surface were directly attributable for the injury rates witnessed, nor did they objectively scrutinise the pitches. This suggests an inherent assumption amongst some researchers that pitches remain constant over time.…”
Section: Current Evidence That Natural Turf Pitches Affect Injury Incmentioning
confidence: 99%
“…16,27,28 Nevertheless, evidence remains indicating persistent differences between injuries sustained on the two different surfaces. [29][30][31][32][33] None of these studies reported what characteristics of the playing surface were directly attributable for the injury rates witnessed, nor did they objectively scrutinise the pitches. This suggests an inherent assumption amongst some researchers that pitches remain constant over time.…”
Section: Current Evidence That Natural Turf Pitches Affect Injury Incmentioning
confidence: 99%
“…Recently, data from Scandinavian male professional football showed that clubs with AT installed at their home arenas had higher general injury rates compared with clubs having NG installed at their home arenas, especially regarding overuse injuries. 3 However, this increased injury rate for AT clubs was evident on both playing surfaces, and it was thus suggested that the higher injury rate could not be attributed to high AT exposure per se, but possibly due to more frequent surface shifts among the AT clubs. Owing to different surfaces at clubs' home venues, shifts between playing surfaces frequently occur in Swedish and Norwegian football.…”
Section: Introductionmentioning
confidence: 99%
“…Pre-season football activities in Sweden and Norway (from the beginning of January to the middle or end of March) are largely carried out indoors or outdoors on AT. 3 Therefore, only the 5 competitive part of each season was included (starting with the primary competition match for each team and season. Injury rate is expressed as the number of injuries/1000 h with 95% CI, using a rate ratio with corresponding 95% CI, and significance was tested with z-statistics.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations